Effects of TiO(2) nanoparticles on nutrition metabolism in silkworm fat body - Tian, J. H. (Biol Open, 2016)
Silkworm (Bombyx mori) is an important economic insect with a fat body that plays a crucial role in the storage and transfer of nutrients. It is also known that TiO(2) nanoparticles (NPs) can improve feed efficiency and promote silk protein synthesis in the silkworm. In this study, we profiled gene expression in the silkworm fat body after TiO(2) NP treatment, validated the major RNA-seq findings, and determined the contents of trehalose and triglyceride, the activity of lipase, and the amount of total proteins. RNA-seq analysis revealed that TiO(2) NP treatment caused significant expression changes in 341 genes (P≤0.01), 138 of which were upregulated while the other 203 were downregulated. The expression levels of two target genes in the insulin signaling pathway and two protein metabolism-related target genes, three lipid metabolism-associated target genes, two carbohydrate metabolism related target genes and expression levels of seven heat shock protein genes were increased, and that of threonine dehydratase gene and fatty acid transport protein gene were decreased. The RNA-seq results of 16 genes were validated by quantitative real-time PCR. The lipase activity, content of trehalose, and amount of total proteins were elevated by 3.86-fold, 1.34-fold, and 1.21-fold, respectively, and the content of triglyceride was decreased by 0.94-fold after TiO(2) NP treatment. These results indicated that TiO(2) NPs activated the insulin signaling pathway, promoted the metabolism of protein, fat, and carbohydrate, and improved nutrition metabolism. Our study provides new support for the understanding of the beneficial effect of TiO(2) NPs on silkworm nutrient metabolism.